Systemic Hyperthermia in Traumatic Brain Injury—Relation to Intracranial Pressure Dynamics, Cerebral Energy Metabolism, and Clinical Outcome. Issue 4 (October 2021) - Svedung Wettervik, Teodor M.; Engquist, Henrik; Lenell, Samuel; Howells, Timothy; Hillered, Lars; Rostami, Elham; Lewén, Anders; Enblad, Per
Abstract : Background: Systemic hyperthermia is common after traumatic brain injury (TBI) and may induce secondary brain injury, although the pathophysiology is not fully understood. In this study, our aim was to determine the incidence and temporal course of hyperthermia after TBI and its relation to intracranial pressure dynamics, cerebral metabolism, and clinical outcomes. Materials and Methods: This retrospective study included 115 TBI patients. Data from systemic physiology (body temperature, blood pressure, and arterial glucose), intracranial pressure dynamics (intracranial pressure, cerebral perfusion pressure, compliance, and pressure reactivity), and cerebral microdialysis (glucose, pyruvate, lactate, glycerol, glutamate, and urea) were analyzed during the first 10 days after injury. Results: Overall, 6% of patients did not have hyperthermia (T>38°C) during the first 10 days after injury, whereas 20% had hyperthermia for >50% of the time. Hyperthermia increased from 21% (±27%) of monitoring time on day 1 to 36% (±29%) on days 6 to 10 after injury. In univariate analyses, higher body temperature was not associated with higher intracranial pressure nor lower cerebral perfusion pressure, but was associated with lower cerebral glucose concentration ( P =0.001) and higher percentage of lactate-pyruvate ratio>25 ( P =0.02) on days 6 to 10 after injury. Higher body temperature and lower arterial glucose concentration were associated with lower cerebral glucose in a multiple linear regression analysis ( P =0.02 for both). There was no association between hyperthermia and worse clinical outcomes. Conclusion: Hyperthermia was most common between days 6 and 10 following TBI, and associated with disturbances in cerebral energy metabolism but not worse clinical outcome.